Performance of Enhanced Finite Element Formulations in Localized Failure Computations - Steinmann, Paul; Willam, Kaspar (Computer Methods in Applied Mechanics and Engineering, 1991)
In the paper we examine the performance of different enhancement strategies for improving low order finite element expansions with respect to their ability to capture discontinuous failure mechanisms. To this end, a 'weak localization test' will be developed for testing single elements, whether they can capture discontinuous bifurcation without directional bias. This weak form of localization is subsequently utilized to generate singularized elements which are designed to reproduce localized failure in a distributed manner. The element study will be complemented by localization studies of an elasto-plastic boundary value problem. This progressive failure example is used to verify the principal results of the weak localization test for single elements with a non-uniform deformation problem exhibiting localized failure. © 1991.
UnivIS-Import:2015-03-05:Pub.1991.tech.FT.FT-TM.perfor